Harry Potter and the chamber of secrets [videorecording (DVD)] - Kloves, Steven; Columbus, Chris; Radcliffe, Daniel, 1989-; Watson, Emma, 1990-; Grint, Rupert, 1988-; Branagh, Kenneth; Cleese, John; Coltrane, Robbie; Davis, Warwick; Griffiths, Richard, 1947-2013; Harris, Richard, 1930-2002; Isaacs, Jason, 1963-; et al. (Warner Home Video, 2003)
Finds young wizard Harry and his friends Ron and Hermoine facing new challenges during their second year at Hogwarts School of Witchcraft and Wizardry as they try to uncover a dark force that is terrorizing the school.